The first substituted macrocyclic ligand Py2N4S2 containing four naphthylmethylene pendant-armed groups: Synthesis and photophysical properties - Catherine De Castro (Inorganic Chemistry Communications, 2013)
The synthesis of a pendant donor emissive macrocyclic ligand Py2N4S2 with up to four naphthylmethylene arms (L) has been achieved. Their derivative solid metal complexes (Co2 +, Ni2 +, Cu2 +, Zn2 +, Cd2 +, Hg2 + and Ag+) have been isolated and characterized. The photophysical properties of the free ligand L and their complexation behaviour have been investigated in solution. In dichloromethane, the free ligand presents two emission bands which are related to the monomer naphthalene emission and a red-shifted band attributable to ground state dimers (interaction between two naphthalene chromophores), which was further validated from time-resolved data, with bi-exponential decay with absence of dynamic components. UV–Vis spectroscopy has revealed a 2:1 binding stoichiometry for Co2 +, Cu2 +, Zn2 +, Hg2 + and Ag+.